ZAKAT PROFESI TERHADAP KESEJAHTERAAN UMAT - Fatimah; Shalihah; Erwan Setyanoor (PT. Saha Kreasi Indonesia, 2026)
Professional zakat represents an advanced development of zakat concepts within the framework of contemporary economic dynamics, positioning income derived from professional activities as a zakatable asset with significant socio-economic implications. This study aims to examine the contribution of professional zakat to the enhancement of community welfare through structured distribution mechanisms and sustainable empowerment programs. The research employs a literature-based approach by reviewing modern fiqh perspectives, Islamic welfare theories, and empirical studies related to the effectiveness of zakat management. The findings indicate that professional zakat functions as a redistributive instrument capable of reducing income inequality, strengthening the economic capacity of beneficiaries, and fostering social stability. Transparent and accountable management by zakat institutions demonstrates its strategic potential in expanding welfare impacts. Accordingly, the optimization of professional zakat can serve as a fundamental pillar for promoting inclusive and equitable economic development within the Muslim community.